2015
DOI: 10.29244/jhi.6.3.161-171
|View full text |Cite
|
Sign up to set email alerts
|

Embriogenesis Somatik Jeruk Keprok (Citrus reticulata L. cv Batu 55) Asal Hasil Perlakuan Kolkisin

Abstract: <p>ABSTRACT</p><p><br />The objective of this study was to obtain the best method of regeneration through somatic embryogenesis of citrus cv Batu 55 from callus resulted from in vitro polyploidization by colchicine. The experiment was conducted at the Laboratory of ICABIOGRAD, Bogor and Tissue Culture Laboratory, Department of Agronomy and Horticulture, Bogor Agricultural University from March 2014 until September 2014. This study consisted of proliferation of embryogenic callus, matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The composition of the medium plays an important role in facilitating successful plant regeneration in citrus species. Several studies have shown that Murashige and Skoog (MS) media modified by Morel & Wetmore vitamins (VMW) are suitable for in vitro growth of citrus, as reported in somatic embryogenesis of mandarin (Purwito et al 2015), somatic embryogenesis from endosperm tissue of C. nobilis (Kosmiatin et al 2014), and in micropropagation and micrografting of Japansche Citroen (Putra et al 2015). Conversely, Murashige & Tucker (MT) medium is also widely utilized in citrus plants, including in vitro propagation of Thomson navel sweet oranges (Esmaeilnia & Dehestani 2015) and embryo rescue in progenies resulting from crosses between mandarin and Carrizo citrange (Kurt & Ulger 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the medium plays an important role in facilitating successful plant regeneration in citrus species. Several studies have shown that Murashige and Skoog (MS) media modified by Morel & Wetmore vitamins (VMW) are suitable for in vitro growth of citrus, as reported in somatic embryogenesis of mandarin (Purwito et al 2015), somatic embryogenesis from endosperm tissue of C. nobilis (Kosmiatin et al 2014), and in micropropagation and micrografting of Japansche Citroen (Putra et al 2015). Conversely, Murashige & Tucker (MT) medium is also widely utilized in citrus plants, including in vitro propagation of Thomson navel sweet oranges (Esmaeilnia & Dehestani 2015) and embryo rescue in progenies resulting from crosses between mandarin and Carrizo citrange (Kurt & Ulger 2019).…”
Section: Introductionmentioning
confidence: 99%